1987
DOI: 10.1111/j.1365-2125.1987.tb03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of felodipine on haemodynamics and exercise capacity in patients with angina pectoris.

Abstract: 1 We studied the effects of adding felodipine to W3-adrenoceptor blockade on haemodynamics and exercise capacity in 14 patients with stable angina pectoris using a placebo controlled double-blind crossover protocol. 2 Felodipine reduced supine and standing systolic pressure by 13% (P < 0.01) and 14% (P < 0.01) respectively and increased supine heart rate 7.4% (P < 0.05). 3 Felodipine at a plasma concentration of 15.5 ± 3.0 nmol 1-1 increased exercise duration by 16% (P < 0.01) but failed to attenuate the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…A modest antianginal effect of felodipine was demonstrated in several clinical studies in patients with coronary artery disease during rest [19] and exercise [17][18][19]. The present study may provide the underlying mechanism of this antianginal effect, suggesting that felodipine could exert its beneficial effects by preventing alpha.,-adrenoceptor-mediated coronary vasoconstriction.…”
Section: Hemodgnamic Effects Of T'elodipinementioning
confidence: 69%
See 1 more Smart Citation
“…A modest antianginal effect of felodipine was demonstrated in several clinical studies in patients with coronary artery disease during rest [19] and exercise [17][18][19]. The present study may provide the underlying mechanism of this antianginal effect, suggesting that felodipine could exert its beneficial effects by preventing alpha.,-adrenoceptor-mediated coronary vasoconstriction.…”
Section: Hemodgnamic Effects Of T'elodipinementioning
confidence: 69%
“…A modest beneficial action of felodipine in exerciseinduced myocardial ischemia was demonstrated in recent clinical studies [17][18][19]. To elucidate the potential underlying mechanism, the present study was performed to investigate the effect of felodipine on coronary resistance and myocardial function during alpha.~-adrenoceptor activation in the presence of a severe coronary stenosis.…”
mentioning
confidence: 96%
“…Detry et al reported an increase in exercise capacity after a single dose of felodipine [5]. Sheridan et al confirmed the increase in exercise capacity after 3 weeks' treatment with felodipine 5 mg b. i. d. in addition to a beta-blocker and GTN [7]. Metcalfe et al also employing felodipine as monotherapy confirmed in a longer term study that a modest increase in exercise capacity can be achieved [8].…”
mentioning
confidence: 74%
“…Felodipine is a calcium antagonist with marked vasodilating properties that has been studied in different clinical conditions such as hypertension ]1-4], angina pectoris [5][6][7], and heart failure [8][9][10]. Its vascular selectivity makes it also useful in patients with severe impairment of myocardial contractility.…”
Section: Abstract Felodipine Congestive Heart Failure Regional Blmentioning
confidence: 99%